Osteoprotegerin, but Not Receptor Activator for Nuclear Factor-κB Ligand, is Associated With Subclinical Coronary Atherosclerosis in HIV-Infected Men. (1st December 2015) - Ketlogetswe, Kerunne S.; McKibben, Rebeccah; Jacobson, Lisa P.; Li, Xuihong; Dobs, Adrian S.; Budoff, Matthew; Witt, Mallory D.; Palella, Frank J.; Kingsley, Lawrence; Margolick, Joseph B.; Post, Wendy S.; Brown, Todd T.
Abstract : Context: Abnormalities in the osteoprotegerin (OPG)/receptor activator of nuclear factor-κB ligand (RANKL) axis have been observed in HIV-infected persons and have been implicated in cardiovascular disease (CVD) pathogenesis in the general population. Objective: To determine associations of serum OPG and RANKL concentrations with HIV infection and subclinical atherosclerosis. Design: Cross-sectional study nested within the Multicenter AIDS Cohort Study. Setting: Four US academic medical centers. Participants: There were 578 HIV-infected and 344 HIV-uninfected men. Main outcome measures: Coronary artery calcium (CAC) was measured by noncontrast cardiac computed tomography, and coronary stenosis and plaque characteristics (composition, presence, and extent) were measured by coronary computed tomography angiography. All statistical models were adjusted for traditional CVD risk factors. Results: OPG concentrations were higher, and RANKL concentrations were lower among HIV-infected men compared with HIV-uninfected men ( P < 0.0001 each). Among HIV-infected men, higher OPG concentrations were associated with the presence of CAC, mixed plaque, and coronary stenosis >50%, but not with plaque extent. In contrast, among HIV-uninfected men, higher OPG concentrations were associated with the extent of both CAC and calcified plaque, but not with their presence. RANKL concentrations were not associated with plaque presence or the extent among HIV-infected men, but among HIV-uninfected men, lower RANKL concentrations were associated with greater extent of CAC and total plaque. Conclusions: OPG and RANKL are dysregulated in HIV-infected men, and their relationship to the presence and extent of subclinical atherosclerosis varies by HIV status. The role of these biomarkers in CVD pathogenesis and risk prediction may be different in HIV-infected men.